Study Socio-Cultural Factors Affecting Drug Use Tendency Based on the Behavioral Bias Approach (Studied in the Youth of Ahwaz) - mohammad ali mombeini; Alihossein Hosseinzadeh; Azita mombeini (توسعه اجتماعی, 2019)
The present study tries to examine the socio-cultural factors influencing drug use tendency among Ahwaz metropolitan youth using a sociological cognitive behavioral approach. The present research method is (scrolling). Therefore, the data collection tools (questionnaire), the statistical population (Ahvaz youth), sampling method (cluster), sample population (384 persons), information analysis method 23 spss software), and time and iocation spatial range (Ahwaz, 2016). The empirical findings of the research indicate that: there is a relationship between demographic variables (age, sex, marriage, education level, income) with drug use tendency. There is a positive and significant relationship between variables such as anomy feeling, feelings of relative deprivation, social isolation, peers, folk beliefs in oral literature and drug addiction tendencies. There is also a negative relationship between variables of religiosity and tendency to drug use. Also, the results of the research show that the extent of (0.569) of variance related to narcotics tendency variable with variables of anomy feeling, religiosity, sense of social isolation, and folk beliefs in oral literature can be explained.